Prevalence of vitamin D deficiency in patients attending outpatient clinic with thyroid disorders in Chitwan Medical College Teaching Hospital - Shrestha, Bidhan; Adhikari, Shital; Piryani, Rano Mal; Sedhain, Arun; Deep, Suresh; Sedhai, Sabina; Dhakal, Harikrishna (Journal of Chitwan Medical College, 2017)
Objectives: Vitamin D deficiency is being studied all over the world and is a global health problem. Recent studies haveshown that Vitamin D may have a significant role in reducing the incidence of autoimmune diseases. This study was conducted to find out the level of Vitamin D in patients with thyroid disorders and compare Vitamin D levels in Anti Tpo positive and negative patients. Subject and Methodology: 60 patients from Chitwan Medical College outpatient clinic were included in the study from February to May 2016. A brief history and clinical examinations were taken from all patients along with laboratory tests for thyroid functions, TPO antibody level of 25(OH) Vitamin D3 level and Serum Calcium level. Results: Both patients of hypothyroidism (autoimmune and nonautoimmune) had severe Vitamin D deficiency. Most of the hyperthyroid cases had Vitamin D insufficiency. Anti TPO positive and negative patients both had Vitamin D deficiency. Conclusion: Our study shows there is significant Vitamin D deficiency in hypothyroidism and hyperthyroidism irrespective of its autoimmunity. This study certainly encourages us to screen Vitamin D and supplement Vitamin D to all thyroid disorders patients.